2015
DOI: 10.1007/s11356-015-5115-1
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls (PCBs) in air and soil from a high-altitude pasture in the Italian Alps: evidence of CB-209 contamination

Abstract: This study analyses the seasonal trend of polychlorinated biphenyls (PCB) concentrations in air and soil from a high-altitude mountain pasture in the Italian Alps. PCB concentrations in soil were generally comparable to background levels and were lower than those previously measured in the same area. Only CB-209 unexpectedly showed high concentrations with respect to the other congeners. GC-MS-MS identification was very clear, rising a new problem of increasing PCB contamination concerning only CB-209, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
(75 reference statements)
0
5
0
1
Order By: Relevance
“…As mentioned above, CB-209 was not detected or its concentration was low in the soil around the industrial area in the previous study ( Table 1 ). Nevertheless, Tremolada et al [ 36 ] found that CB-209 unexpectedly showed high concentrations (31–364 pg/g) with respect to the other congeners in soil from a high-altitude mountain pasture in the Italian Alps. On the other hand, some other studies have reported high proportions of CB-209 in water and sediment samples.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, CB-209 was not detected or its concentration was low in the soil around the industrial area in the previous study ( Table 1 ). Nevertheless, Tremolada et al [ 36 ] found that CB-209 unexpectedly showed high concentrations (31–364 pg/g) with respect to the other congeners in soil from a high-altitude mountain pasture in the Italian Alps. On the other hand, some other studies have reported high proportions of CB-209 in water and sediment samples.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison between measured and predicted concentration in air was not possible for the most abundant congener in soil (PCB 209) because it was not present in the measured concentrations dataset (Colombo et al, 2013). However, PCB 209 was found (Tremolada et al, 2015) in soil samples of the Andossi Plateau, a mountain location about 150 km away from the Brescia site. Given the lack of PCB 209 in Fenclor and Aroclor mixtures (apart from Fenclor DK) this can be a confirmation of the possibility that the Brescia site could be the origin of PCB 209 found.…”
Section: Comparison Between Pcb Fingerprints Of Measured Samples and Predicted Datamentioning
confidence: 99%
“…Os PCBs constituem um conjunto de óleos sintéticos composto por substâncias organocloradas, sendo que uma molécula pode variar consideravelmente no que se refere à quantidade de cloro em sua estrutura. Enquadram-se como substâncias sintéticas compondo os doze poluentes orgânicos persistentes (POPs) no âmbito da Convenção de Estocolmo (MARCÍLIO et al, 2014) , 2000;CHATZIKOSMA e VOUDRIAS, 2007;SOBEK et al, 2015;TREMOLADA et al, 2015), desencadeando doenças graves (SOUZA e SMITH, 2013). As ocorrências obtidas foram preliminarmente analisadas mediante a averiguação do título, resumo e palavras-chaves, visando verificar se o objetivo e a metodologia predominantes de cada pesquisa se encaixavam no propósito do presente trabalho.…”
Section: Introductionunclassified